Public Pension Expenditures in Latin America and Projections to 2075: Evidence from Chile, Peru, Colombia, and Mexico - Bernal, Noelia (2016)
This paper analyzes the main factors behind pension expenditures and projects their evolution to 2075 in four Latin American countries: Chile, Peru, Colombia, and Mexico. Pension expenditures are defined as those included in the national budget and allocated to specific benefit plans and to non-contributory pensions. Using a model developed by Clements et al. (2013), it was found that, currently, expenditures are between 1.8 and 6.4 percent of GDP. However, they will rise between 2 and 4 times by 2075, mainly due to population aging. Two simulations were conducted. The first boosted the aging process while the second assumed universal coverage of non-contributory pensions. Expenditures significantly increased in both scenarios and it is recommended that countries pay more attention to aging and its consequences in the long run, especially to the fiscal sustainability of pension systems, in order to permanently estimate pension liabilities, improve accounting, and to build up reserve funds.